The Necessity for Regulating the Insurance Market Considering the Implementation of the IDD - Victoria Petsch (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
In 2018, the Insurance Distribution Directive (IDD) was fully implemented by all EU member states. It intends to harmonize the insurance market, provide the right incentives for the agents and protect the consumers. But why? The core business of the banking sector makes it necessary for a prudential authority to intervene and monitor. The question arises if the latest changes in the insurance business require these limitations and monitoring. This paper offers a literature review by compiling findings and setting up profound arguments, why the regulation of insurance companies is relevant. The main arguments for a strong prudential regulation are transparency, information asymmetry and agency problems, wrong incentives, a representation of the policyholder and the inversion of the production cycle. These findings make it necessary to regulate the companies and protect the policyholders. Further research should focus on case studies of insurance companies implementing the changes of IDD into daily business.
Keywords: G22; G28; G02; G15; 330; Insurance Regulation; Prudential Authority; IDD